Too Exhausted to Perform at the Highest Level? On the Importance of Self-control Strength in Educational Settings - Englert, Chris; Zavery, Alafia; Bertrams, Alex (Frontiers in Psychology, 2017)
In order to perform at the highest level in educational settings (e.g., students in testing situations), individuals often have to control their impulses or desires (e.g., to study for an upcoming test or to prepare a course instead of spending time with the peer group). Previous research suggests that the ability to exert self-control is an important predictor of performance and behavior in educational contexts. According to the strength model, all self-control acts are based on one global energy pool whose capacity is assumed to be limited. After having performed a first act of self-control, this resource can become temporarily depleted which negatively affects subsequent self-control. In such a state of ego depletion, individuals tend to display impaired concentration and academic performance, fail to meet academic deadlines, or even disengage from their duties. In this mini-review, we report recent studies on ego depletion which have focused on children as well as adults in educational settings, derive practical implications for how to improve self-control strength in the realm of education and instruction, and discuss limitations regarding the assumptions of the strength model of self-control.